Process evaluation and lessons learned from the formation of a multi-sector partnership: the Healing Experiences of Adversity among Latinos (HEALthy4You) - Viglione, Clare; Westermann, Amy; Godino, Job; Rhee, Kyung E.; Melendrez, Blanca; Tu, Xin M.; Boyle, David L.; Hogarth, Michael; Aarons, Gregory A.; Crespo, Noe C.; Gidwani, Pradeep; Holguin, Margarita; et al. (Frontiers in Health Services, 2025)
The Healing Experiences of Adversity Among Latinos (HEALthy4You; H4Y) study was a multi-sector partnership between an academic research institution, a Federally Qualified Health Center (FQHC), and a multi-sector collective impact coalition focused on childhood obesity prevention. The goal of HEALthy4You was to develop community-centered and culturally appropriate precision interventions within FQHCs for Latino families to address predictors of adverse child experiences and treat childhood obesity. A multidisciplinary and multi-sector research, clinical, and community team (N = 29) was formed in September 2020 to co-design the study, which launched in June 2022. The team utilized a co-creation approach combined with the Exploration, Preparation, Implementation, and Sustainment framework to facilitate a collaborative design process. We conducted an internal and retrospective process evaluation in March 2023 to identify antecedents and situational factors associated with project formation, with a focus on understanding tensions and challenges with a broad partnership structure. We outline the team's co-creation process and describe internal challenges and pitfalls that emerged when developing the project. We sought to better understand the impact of differing perspectives, priorities, and goals between disciplines, sectors, and roles; differing approaches to evidence and evidence production; and team strategies to mitigate and manage competing pressures and priorities. This case report describes lessons learned, intending to share insights to support future development of best practices in project, partner, and team formation between researchers, clinicians, and community members. More specifically, these lessons could help inform community-led research endeavors between academic institutions, FQHCs, and community-based organizations (CBOs).